2014
DOI: 10.1002/smll.201400292
|View full text |Cite
|
Sign up to set email alerts
|

Configurable Three‐Dimensional Boron Nitride–Carbon Architecture and Its Tunable Electronic Behavior with Stable Thermal Performances

Abstract: Recent developments of 3D-graphene and 3D-boron-nitride have become of great interest owing to their potential for ultra-light flexible electronics. Here we demonstrate the first synthesis of novel 3D-BNC hybrids. By specifically controlling the compositions of C and BN, new fascinating properties are observed, such as highly tunable electrical conductivity, controllable EMI shielding properties, and stable thermal conductivity. This ultra-light hybrid opens up many new applications such as for electronic pack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
73
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 55 publications
8
73
0
Order By: Relevance
“…Yin et al adapted a similar approach to produce three-dimensional h-BN networks, with reported strut wall thickness values from 5 to 50 nm [14]. Loeblein et al used CVD with controllable precursors to achieve networks of varying carbon/h-BN composition, with reported strut wall thickness of *13 atomic layers [15] for 100 % boron nitride samples corresponding to *4-5 nm. These previous works utilized low pressure CVD (LPCVD) processes similar to those used to produce monolayer and few-layer planar 2D materials [16][17][18].…”
Section: Introductionmentioning
confidence: 98%
“…Yin et al adapted a similar approach to produce three-dimensional h-BN networks, with reported strut wall thickness values from 5 to 50 nm [14]. Loeblein et al used CVD with controllable precursors to achieve networks of varying carbon/h-BN composition, with reported strut wall thickness of *13 atomic layers [15] for 100 % boron nitride samples corresponding to *4-5 nm. These previous works utilized low pressure CVD (LPCVD) processes similar to those used to produce monolayer and few-layer planar 2D materials [16][17][18].…”
Section: Introductionmentioning
confidence: 98%
“…[21][22][23][24][25][26] Therefore, they are suitable in applications of electronic devices, aircrafts electronics and automobiles. Generally, the main restriction for ceramics as efficient shielding materials is their low electrical conductivity.…”
mentioning
confidence: 99%
“…Email: hbzhang@caep.cn, pengshuming@caep.cn electrical conductivity and EMI SE of ceramics could also be significantly enhanced by incorporating highly conducting CNTs or carbon fibers. [21][22][23][24][25][26] Xiang et al 21 prepared CNTs reinforced fused silica composites and a high SE of 68 dB at 36-37 GHz was obtained with 10 vol% CNTs. Shi et al 22 investigated the effect of CNTs on the shielding properties of yttria-stabilized zirconiain in the Ku-band range and an EMI SE value as high as 25-30 dB was achieved.…”
mentioning
confidence: 99%
“…For instance, graphenecarbon nanotube 3D structures had densities as low as 0.16 mg cm − 3 , even lighter than air (1.29 mg cm − 3 ); 9 3D graphene and BN networks exhibited excellent mechanical properties; 10,11 3D BNC hybrid networks showed tunable electronic and thermal properties. 12 However, the high-yield fabrication of such 3D architectures of 2D crystals, especially without using any templates or catalysts, remains a great challenge. Currently, there are two methods for fabricating 3D WG foams.…”
Section: Introductionmentioning
confidence: 99%
“…This chemical vapor deposition approach can provide high mechanical and electrical properties and hence has attracted much interest in energy devices. 11,12,17 However, the yield and cost is limited by the use of Ni foams. According to the current state in this field, the realization of high-yield and natural connections will greatly advance 3D WG foams.…”
Section: Introductionmentioning
confidence: 99%